Mixed corticomedullary tumor of the adrenal gland - Kimura, Noriko; Motoyama, Teiich; Saito, Jun; Nishikawa, Tetsuo (Frontiers in Endocrinology, 2022)
Mixed corticomedullary tumor (MCMT) of the adrenal gland is an extremely rare tumor characterized by an admixture of steroidogenic cells and chromaffin cells in a single tumor mass simultaneously producing adrenocortical hormones and catecholamines; it is associated with ectopic adrenocorticotropic hormone (ACTH) in some cases. We reviewed and summarized clinicopathological data of 28 MCMTs, including four metastatic tumors in 26 previous reports. These reports included 21 females and 7 males, and the average tumor sizes were 4.8 ± 2.5 cm and 12.6 ± 6.4 cm in the non-metastatic and metastatic groups, respectively (P<0.001). The clinical manifestations and laboratory data were as follows: Cushing or subclinical Cushing syndrome, 58% (14/24); hypertension, 71% (17/24); elevated adrenocortical hormones, 75% (18/24); elevated catecholamines, 75% (18/24); and ectopic ACTH, 71% (10/14). All four patients with metastatic MCMTs had poor prognoses and elevated adrenocortical hormone levels; however, only two patients had elevated catecholamine levels. Immunohistochemistry was essential for the pathologic diagnosis of MCMTs. In this study, using an improved technique, we detected ectopic ACTH-producing cells in the same paraffin-embedded sections reported to be negative in our previous reports. As MCMT is composed of cells with embryologically different origins, its pathogenesis has been explained by various hypotheses. We compared MCMT to the adrenal gland of birds and the early stage of human fetuses, in which nests of chromaffin cells and steroidogenic cells admix without the formation of cortex and medulla. MCMT is characterized by the immaturity of organogenesis and might be classified as an adrenal embryonal tumor.